COGNITIVE LEVEL ANALYSIS OF ENGLISH TEST ITEMS: A CASE OF A GRADE VII SUMMATIVE TEST - Andrean Tirta Wijaya; Diah Kurniati; Fitri Budi Suryani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Assessment in English learning reflects not only students' language achievement but also the cognitive demands developed through the instructional process. This qualitative descriptive study aims to analyze the distribution of cognitive levels of seventh-grade English summative test items based on the Revised Bloom's Taxonomy and to evaluate the extent to which the items train higher-order thinking skills (HOTS). The research data comes from a final semester summative test instrument that analyzes 45 items, consisting of 35 multiple-choice items, 5 complex multiple-choice items, and 5 essay items. Each item is classified into six cognitive levels through careful analysis of the instrument's checklist. The results show that the test instrument covers all cognitive levels with a distribution of remembering C1 of 4.4 percent (2 items), understanding C2 of 22.2 percent (10 items), applying C3 of 11.1 percent (5 items), analyzing C4 of 44.4 percent (20 items), evaluating C5 of 6.7 percent (3 items), and creating C6 of 11.1 percent (5 items). The HOTS portion (C4–C6) reached 62.2 percent, with the analysis level dominating in reading comprehension and the creation level in the essay section. The main conclusion confirms that this summative test instrument is largely aligned with HOTS principles, but a more balanced distribution of cognitive levels is recommended by increasing the portion of questions at the evaluation level. ABSTRAK Penilaian dalam pembelajaran bahasa Inggris tidak hanya mencerminkan pencapaian berbahasa siswa tetapi juga tuntutan kognitif yang dikembangkan melalui proses instruksional. Penelitian deskriptif kualitatif ini bertujuan menganalisis sebaran tingkat kognitif butir soal tes sumatif bahasa Inggris kelas VII berdasarkan Taksonomi Bloom Revisi serta mengevaluasi sejauh mana soal melatih keterampilan berpikir tingkat tinggi (higher-order thinking skills atau HOTS). Data penelitian bersumber dari instrumen tes sumatif semester akhir yang menganalisis 45 butir soal, terdiri atas 35 pilihan ganda, 5 pilihan ganda kompleks, dan 5 esai. Setiap butir soal diklasifikasikan ke dalam enam tingkat kognitif melalui analisis lembar centang instrumen secara cermat. Hasil penelitian menunjukkan instrumen tes mencakup seluruh tingkat kognitif dengan sebaran mengingat C1 sebesar 4,4 persen (2 soal), memahami C2 sebesar 22,2 persen (10 soal), menerapkan C3 sebesar 11,1 persen (5 soal), menganalisis C4 sebesar 44,4 persen (20 soal), mengevaluasi C5 sebesar 6,7 persen (3 soal), dan mencipta C6 sebesar 11,1 persen (5 soal). Porsi HOTS (C4–C6) mencapai 62,2 persen dengan dominasi tingkat menganalisis pada pemahaman membaca, serta tingkat mencipta pada bagian esai. Simpulan utama mengonfirmasi bahwa instrumen tes sumatif ini telah sebagian besar selaras dengan prinsip HOTS, namun disarankan adanya distribusi tingkat kognitif yang lebih seimbang melalui penambahan porsi soal pada tingkat mengevaluasi.